Bank consolidation and new business formation - Francis, Bill; Hasan, Iftekhar; Wang, Haizhi (Journal of Banking & Finance, 2008)
As the trend of bank consolidation activities continues to grow in the US and globally, the debate on the impact of such consolidation on small business credits and activities are still inconclusive. Building on the existing research [Berger, A.N., Saunders, A., Scalise, J.M., Udell, G.F., 1998. The effects of bank mergers and acquisitions on small business lending. Journal of Financial Economics 50, 187–229]; [Black, S.E., Strahan, P.E., 2002. Entrepreneurship and bank credit availability. Journal of Finance LVII (6), 2807–2833], this paper investigates the effects of the actual intensity of bank consolidation on the formation of new businesses in the US local markets. Evidence portrays that in the short-run, the overall intensity of bank consolidation is negatively related to the rate of new business formation, and this negative relationship is primarily driven by consolidations initiated by large acquirers. On the contrary, consolidations between small-to-medium sized banks show a positive impact on new business development and these results are consistent even when the M&As are distinguished with respect to in-market or out-of-market acquirers initiating the deals. However, two years after the consolidations, the evidence reveals a positive and significant impact on the rate of new business formation in the local markets for consolidations initiated by large in-market acquirers.